Deciphering the mechanisms, hormonal signaling, and potential applications of endophytic microbes to mediate stress tolerance in medicinal plants - Pandey, Praveen; Tripathi, Arpita; Dwivedi, Shweta; Lal, Kanhaiya; Jhang, Tripta (Frontiers in Plant Science, 2023)
The global healthcare market in the post-pandemic era emphasizes a constant pursuit of therapeutic, adaptogenic, and immune booster drugs. Medicinal plants are the only natural resource to meet this by supplying an array of bioactive secondary metabolites in an economic, greener and sustainable manner. Driven by the thrust in demand for natural immunity imparting nutraceutical and life-saving plant-derived drugs, the acreage for commercial cultivation of medicinal plants has dramatically increased in recent years. Limited resources of land and water, low productivity, poor soil fertility coupled with climate change, and biotic (bacteria, fungi, insects, viruses, nematodes) and abiotic (temperature, drought, salinity, waterlogging, and metal toxicity) stress necessitate medicinal plant productivity enhancement through sustainable strategies. Plants evolved intricate physiological (membrane integrity, organelle structural changes, osmotic adjustments, cell and tissue survival, reclamation, increased root-shoot ratio, antibiosis, hypersensitivity, etc.), biochemical (phytohormones synthesis, proline, protein levels, antioxidant enzymes accumulation, ion exclusion, generation of heat-shock proteins, synthesis of allelochemicals. etc.), and cellular (sensing of stress signals, signaling pathways, modulating expression of stress-responsive genes and proteins, etc.) mechanisms to combat stresses. Endophytes, colonizing in different plant tissues, synthesize novel bioactive compounds that medicinal plants can harness to mitigate environmental cues, thus making the agroecosystems self-sufficient toward green and sustainable approaches. Medicinal plants with a host set of metabolites and endophytes with another set of secondary metabolites interact in a highly complex manner involving adaptive mechanisms, including appropriate cellular responses triggered by stimuli received from the sensors situated on the cytoplasm and transmitting signals to the transcriptional machinery in the nucleus to withstand a stressful environment effectively. Signaling pathways serve as a crucial nexus for sensing stress and establishing plants’ proper molecular and cellular responses. However, the underlying mechanisms and critical signaling pathways triggered by endophytic microbes are meager. This review comprehends the diversity of endophytes in medicinal plants and endophyte-mediated plant-microbe interactions for biotic and abiotic stress tolerance in medicinal plants by understanding complex adaptive physiological mechanisms and signaling cascades involving defined molecular and cellular responses. Leveraging this knowledge, researchers can design specific microbial formulations that optimize plant health, increase nutrient uptake, boost crop yields, and support a resilient, sustainable agricultural system.